Expectations in Export Price Formation Tests using Cointegrated VAR Models - Pål Boug; Ådne Cappelen; Anders R. Swensen (Statistics Norway, Research Department, 2000)
The formation of export prices is an area in which the linear quadratic adjustment cost (LQAC) model under rational expectations may be relevant in practice. This paper evaluates the empirical performance of the LQAC-model using Norwegian data and a new testing procedure suggested by Johansen and Swensen (1999). We find, however, that the model can be rejected for our data set. Conversely, we show in light of Hendry (1988) that there exists a data-coherent conditional equilibrium correction (EqCM) model, which is not subject to the Lucas critique. Our findings do not support the claim that Norwegian exporters act on expectations based models in the formation of prices.
Keywords: C51; C52; D84; E31; 330; Expectations; export prices; LQAC-model; cointegrated VAR; EqCM-model; exogeneity; Lucas critique.